2022
DOI: 10.1177/07356331211053848
|View full text |Cite
|
Sign up to set email alerts
|

Entertainment Video Games for Academic Learning: A Systematic Review

Abstract: Entertainment video games are very popular among young audiences. Nevertheless, despite their potential to improve cognitive functioning, they are still studied rarely as a tool for digital game-based learning. To better understand video gaming practices’ value in the classroom, this article provides a systematic review of literature on the effect of entertainment video games on academic learning. Our literature search yielded 49 relevant intervention studies published between 2005 and 2019 that integrated ent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(35 citation statements)
references
References 83 publications
(110 reference statements)
0
32
0
3
Order By: Relevance
“…A review by Pan et al ( 2022 ) that examined the role of learning games in fostering mathematics education in K-12 settings, reported that gameplay improved students’ performance. Integration of digital games in teaching was also found as a promising pedagogical practice in STEM education that could lead to increased learning gains (Martinez et al, 2022 ; Wang et al, 2022 ). However, although Talan et al ( 2020 ) reported a medium effect of the use of educational games (both digital and non-digital) on academic achievement, the effect of non-digital games was higher.…”
Section: Resultsmentioning
confidence: 99%
“…A review by Pan et al ( 2022 ) that examined the role of learning games in fostering mathematics education in K-12 settings, reported that gameplay improved students’ performance. Integration of digital games in teaching was also found as a promising pedagogical practice in STEM education that could lead to increased learning gains (Martinez et al, 2022 ; Wang et al, 2022 ). However, although Talan et al ( 2020 ) reported a medium effect of the use of educational games (both digital and non-digital) on academic achievement, the effect of non-digital games was higher.…”
Section: Resultsmentioning
confidence: 99%
“…The COVID-19 pandemic defined the role digital technologies can play in education and their relationships with teacher training, the flexibility of pedagogical processes, and the diversification of strategies and resources [30]. The study of [31] underlines that entertainment video games can be an effective educational tool and beneficial in almost all academic disciplines, particularly foreign language and science. Digital educational games (DEGs) constitute an effective teaching approach, particularly when combined with collaborative learning scenarios.…”
Section: Literature Reviewmentioning
confidence: 99%
“…For this reason, research on game-based learning has investigated for over three decades how to develop and use games specifically designed to promote desirable learning (Abt, 1987; Avila-Pesantez et al, 2017; De Freitas, 2018; Fabricatore et al, 2020; Rieber, 1996; Squire, 2005). In parallel with this attention to educational games, there is also growing interest in entertainment games (i.e., commercial digital entertainment products designed for recreational purposes) and how they can be used to promote meaningful learning (Clark et al, 2016; Jayakanthan, 2002; Martinez et al, 2022; McClarty et al, 2012; Paraskeva et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Gameplay learning is fully intrinsically motivated, i.e., it is motivated solely by the goals, contextu- alizations, and mechanics that games provide (Egenfeldt-Nielsen, 2006; Fabricatore, 2000; Gee, 2003; Mitchell & Savill-Smith, 2004; Prensky, 2002) and, thus, it represents an optimal learning experience (Habgood et al, 2005; Guay et al, 2008; Malone & Lepper, 1987; Shernoff & Csikszentmihalyi, 2009). The combination of these factors (i.e., transferability to out-of-game contexts, intrinsic moti- vation, and integrative development of knowledge, attitudes, and skills) make gameplay learning a particularly relevant form of learning to investigate, emphasizing the importance of understanding which features can make entertainment games enjoyable and at the same time suitable for promoting learning processes and outcomes relevant to contexts outside the game (Boyle et al, 2016; Clark et al, 2016; Connolly et al, 2012; Granic et al, 2014; Martinez et al, 2022; Prensky, 2002).…”
Section: Introductionmentioning
confidence: 99%